2009
DOI: 10.1080/14681990802666023
|View full text |Cite
|
Sign up to set email alerts
|

Mind your language: working with interpreters in healthcare settings and therapeutic encounters

Abstract: national and international consultancy work and training work with a range of organisations. Her clinical and research interests focus on all aspects of trauma, culture and mental health, professional and ethical practice, working with interpreters in mental health, the mental health of refugees, and asylum seekers and organisational development.Aneta Tunariu is a principal lecturer in psychology at the University of East London and field leader for programmes in guidance, counselling and coaching. She also wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…Because of the changing boundaries of medicine, culture, and language in bilingual medical encounters, providers and interpreters often need to negotiate their roles, responsibilities, and expertise [5]. Although our findings suggest providers have used interpreters mostly as passive instruments, expecting interpreters to “don’t speak unless spoken to” fails to recognize the complex utility an interpreter can offer in culturally sensitive care [16, 24]. When interpreters are viewed as smart technology, there will be a mutual-learning process between the interpreter and the provider.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the changing boundaries of medicine, culture, and language in bilingual medical encounters, providers and interpreters often need to negotiate their roles, responsibilities, and expertise [5]. Although our findings suggest providers have used interpreters mostly as passive instruments, expecting interpreters to “don’t speak unless spoken to” fails to recognize the complex utility an interpreter can offer in culturally sensitive care [16, 24]. When interpreters are viewed as smart technology, there will be a mutual-learning process between the interpreter and the provider.…”
Section: Discussionmentioning
confidence: 96%
“…Extensive research has been conducted surrounding the issues presented when a hearing person who requires an interpreter meets a therapist within a therapeutic encounter (Tribe & Tunariu, 2009). However, sign language is unique in that it is a multidimensional, visual-gestural language which distinguishes it from verbal languages.…”
mentioning
confidence: 99%
“…A systematic review conducted by Karliner, Jacobs, Chen, and Mutha (2007) found that the use of trained interpreters in healthcare settings vastly improves the quality of service delivery to the extent that it approaches and in some instances equals that for clients without language barriers. Research has found that the use of trained interpreters contributes to improved service delivery through improved communication, clinical outcomes, and users’ satisfaction with care (Tribe & Tunariu, 2009; Yakushko, 2010). Furthermore, trained interpreters are more likely to have adequate knowledge of medical terms and less likely to commit interpretation errors.…”
Section: Interpreters In Health Carementioning
confidence: 99%
“…When no staff member is available, healthcare practitioners often find themselves reliant on family members to translate, which can obstruct objectivity and have serious ethical implications (Fatahi et al, 2008). The use of untrained interpreters further potentiates the deleterious effects already inherent in this process; several studies have suggested that the use of ad hoc interpreters increases the risk of serious adverse outcomes resultant from miscommunication, misdiagnosis, and inadequate roll-out of treatment plans (Tribe & Tunariu, 2009). Although the monetary cost of using professionally trained interpreters is a significant barrier to use, particularly in countries with limited resources, it should be noted that the consequence of using untrained interpreters is less explored and could potentially be more costly in the long term (Ku & Flores, 2005; Smith & Claire, 2008).…”
Section: Interpreters In Health Carementioning
confidence: 99%